Collection Time, Location, and Mosquito Species Have Distinct Impacts on the Mosquito Microbiota - Pérez-Ramos, Daniel W.; Ramos, Martina M.; Payne, Kyle C.; Giordano, Bryan V.; Caragata, Eric P. (Frontiers in Tropical Diseases, 2022)
The mosquito microbiota affects many aspects of mosquito biology including development and reproduction. It also strongly impacts interactions between the mosquito host and pathogens that cause important disease in humans, such as dengue and malaria. Critically, the mosquito microbiota is highly diverse and can vary in composition in response to multiple environmental variables, but these effects are not always consistent. Understanding how the environment shapes mosquito microbial diversity is a critical step in elucidating the ubiquity of key host-microbe-pathogen interactions in nature. To that end, we examined the role of time of collection, collection location and host species on mosquito microbial diversity by repeating collections at two-month intervals on a trapping grid spanning three distinct biomes. We then used 16S rRNA sequencing to compare the microbiomes of Aedes taeniorhynchus, Anopheles crucians, and Culex nigripalpus mosquitoes from those collections. We saw that mosquito diversity was strongly affected by both time and collection location. We also observed that microbial richness and diversity increased from March to May, and that An. crucians and Cx. nigripalpus had greater microbial diversity than Ae. taeniorhynchus. However, we also observed that collection location had no impact on microbial diversity except for significantly lower bacterial richness observed in mosquitoes collected from the mangrove wetlands. Our results highlight that collection time, collection location, and mosquito species each affect aspects of mosquito microbial diversity, but their importance is context dependent. We also demonstrate that these variables have differing impacts on mosquito diversity and mosquito microbial diversity. Our findings suggest that the environment likely plays an important but variable role in influencing the composition of the mosquito microbiota.